An approach to monitor the real-time deformation during heat treatment of 3D-printed glass. Issue 14 (15th July 2021) - Hmood, Firas J.; Wilbig, Janka; Nicolaides, Dagmar; Zocca, Andrea; Günster, Jens
Abstract: This study suggests a tool for a better control on the sintering/crystallization of 3D-printed bioactive glass-ceramics bodies. A small cantilever in form of a bar with square cross section attached to a base and inclined 34° with the horizon, was used to monitor the viscous flow and sintering/crystallization headway of a glass-ceramic systems. 3D printing and sintering of bioactive glass-ceramics is of great interest for medical care applications. Viscous flow ensures sufficient densification of the typically low density printed green bodies, while crystallization prevents the structure from collapsing under the gravitational load. As a model system, a bioactive glass called BP1 (48.4 SiO2, 1 B2 O3, 2 P2 O5, 36.6 CaO, 6.6 K2 O, 5.6 Na2 O (mol%)), which has a chemical composition based on that of ICIE16, was employed in this work. In addition, ICIE16 was used as a reference glass. The results show that the suggested design is a very promising tool to track the real-time deformation of 3D printed glass-ceramic specimens and gives a good indication for the onset of crystallization as well.